A comparative study on male rape in Malaysia and other jurisdictions / Adzim Amir Hamzah, Suzalena Salleh and Azmahanim Azman Shah - Hamzah, Adzim Amir; Salleh, Suzalena; Azman Shah, Azmahanim (2006)
For the last two semesters we have been conducting a research on the law of male rape in Malaysia and other jurisdictions namely in United Kingdom, United States, Singapore and Australia. In our research we concentrated on both form of the crime which is sodomy and female raping male issue. Seemingly, the latter form of male rape is being taken lightly around the world. Nonetheless we found that the law of sodomy is getting the recognition it deserved although the development has been slow and still in some area, insufficient. Therefore it is fundamental for a research to be conducted on this topic. The importance of enacting such laws therefore can be analyzed as a whole. In Malaysia, we have tried to analyze and discuss Section 377 of the Penal Code thoroughly in order to ascertain its effectiveness in combating the crime of sodomy. The result is in the negative. Thus, amending the section or enacting a new and more extensive law is practical and much needed. In completing our project paper, we have distributed questionnaires concerning male rape to 400 respondents. The outcome of the questionnaires is as we expected. A majority of the respondents is aware of such crime but still obscure regarding the law that govern the offence. Among the important questions that were asked in the questionnaires was whether the respondents are aware that a female rapist may escape scot-free from the crime of male rape and whether a specific provision on male rape should be enacted in the Penal Code. We benefited a lot from the answers that we managed to gather through the questionnaires. However, our research is also based on our readings of various books and materials that we find in online. After two semesters, we finally finished doing our project paper on a comparative study on the law of male rape in Malaysia and other jurisdictions.